2007
DOI: 10.1071/ea06085
|View full text |Cite
|
Sign up to set email alerts
|

Comparing irrigated biodynamic and conventionally managed dairy farms. 2. Milk production and composition and animal health

Abstract: Ten paired irrigated dairy farms under biodynamic (BD) and conventional (CV) management were compared over a 3-year period (1991–93). The paired farms were located in the irrigation districts of northern Victoria and southern New South Wales and were matched for soil type, cattle breed and farm area. The BD farms practised BD principles for an average of 16 years before the study. The effects of farm management on milk yields and composition and animal health were examined by annually surveying farm managers r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Potassium, sodium, and chloride analyses were carried out using electrode methods (Zannier et al ., 2002). Calcium analyses used the Arsenazo III method (Burkitt et al ., 2007). Inorganic phosphorus analyses were carried out by the molybdic-acid direct method (Burkitt et al ., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Potassium, sodium, and chloride analyses were carried out using electrode methods (Zannier et al ., 2002). Calcium analyses used the Arsenazo III method (Burkitt et al ., 2007). Inorganic phosphorus analyses were carried out by the molybdic-acid direct method (Burkitt et al ., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, earthworm biomass was greater in the CON system on account of one earthworm species, where no information was given on the number of earthworms. Burkitt et al 31 also report lower milk yields on BD farms on a per hectare and per cow basis. A significantly greater number of chemical treatments per cow were used on CON farms.…”
Section: Case Studies Of Production Systemsmentioning
confidence: 95%
“…Information on incidences of clinical mastitis and longevity of animals, however, is not provided. Burkitt et al 31 suggested the use of certified inputs on BD farms to increase milk fat, protein and production levels, but did not give further details. This was the only published study found that dealt with farm animals and BD farming practices; thus a serious lack of research projects/results is found and research in this area is strongly encouraged.…”
Section: Case Studies Of Production Systemsmentioning
confidence: 99%
“…We recognize the importance of efficiently using inputs and not over‐supplying, but – clearly – the high‐yielding agricultural systems for sustainable intensification and global food security must involve abundant nutrient inputs if crops are to achieve maximal yields, as these entail high nutrient outputs in produce. If nutrient inputs, including phosphorus (P), are less than outputs in produce, yields will inevitably decline: abundant AMF will not maintain yields (Ryan et al ., ; Burkitt et al ., ). In Africa, where the need for improved food security is greatest (Fischer & Connor, ), addressing this relationship through increased inputs is essential (Craswell & Vlek, ).…”
Section: A Response To Rillig Et Al (2019) ‘Why Farmers Should Managmentioning
confidence: 99%